2005
DOI: 10.1159/000088442
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Subjective Experience among First-Admitted Schizophrenia Spectrum Patients: Empirical Investigation

Abstract: Our research group has for several years conducted philosophically informed, phenomenological-empirical studies of morbid alterations of conscious experience (subjectivity) in schizophrenia (Sz) and its spectrum of disorders. Some of these experiential alterations constitute, in our view, the vulnerability markers to Sz – indicators that are intrinsic to this disorder and which were historically considered as constituting the phenotypic anchor of the very concept and the diagnostic validity of Sz spectrum diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
143
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 152 publications
(157 citation statements)
references
References 43 publications
10
143
0
4
Order By: Relevance
“…A body of phenomenological research, combining clinical exploration, empirical studies and philosophical perspectives, indicates that a disturbance of the basic sense of self is at the clinical core of the schizophrenia spectrum and may therefore function as a phenotypic trait marker of these disorders, including vulnerability not (yet) expressed at diagnosable levels [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. What exactly is being referred to "basic" sense of self?…”
Section: The Phenomenological Domain: Basic Self-disturbance In Schizmentioning
confidence: 99%
“…A body of phenomenological research, combining clinical exploration, empirical studies and philosophical perspectives, indicates that a disturbance of the basic sense of self is at the clinical core of the schizophrenia spectrum and may therefore function as a phenotypic trait marker of these disorders, including vulnerability not (yet) expressed at diagnosable levels [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. What exactly is being referred to "basic" sense of self?…”
Section: The Phenomenological Domain: Basic Self-disturbance In Schizmentioning
confidence: 99%
“…10 A series of subsequent systematic empirical studies demonstrated that SDs aggregate selectively in first-admission schizophrenia and schizotypal disorders [11][12][13] but not in bipolar psychosis. 14,15 SDs are detectable in populations at high-genetic risk for schizophrenia 13 and are associated with prodromal symptoms among help-seeking, non-psychotic adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, SDs are shared by schizophrenia and schizotypal disorders, with no significant differences between these two diagnostic groups. 11,12,27 In the Copenhagen Linkage Study, SDs distinguished healthy high-risk individuals who exhibited few schizotypal features from healthy high-risk subjects with no schizotypal features. 40 In sum, our results, in conjunction with other SD studies, strengthen the rationale for a further exploration of the SDs as a potentially core phenotype of schizophrenia-spectrum disorders and its predictive utility in the prodromal research.…”
mentioning
confidence: 99%
“… Self-disorders hyper-aggregate in schizophrenia spectrum disorders but not in other mental disorders [39][40][41][42][43]  There is no statistical difference in the level of selfdisorders among patients with schizophrenia and patients with the schizotypal disorder [41,43]  Self-disorders differentiate between first-admitted cases with bipolar psychosis and schizophrenia [42] and self-disorders occur more frequently in residual schizophrenia than in remitted bipolar psychosis [44]  Self-disorders occur in genetically high-risk individuals [45]  Self-disorders are detectable in community samples of adolescent diagnosed as suffering from "at-risk mental state" [46] and in clinical samples of young adults at Clinical High Risk for psychosis [47]  Prospective studies indicate that self-disorders predict transition to psychosis in an Ultra-High Risk for psychosis sample [48] and that high baseline scores of self-disorders predict later transition to a schizophrenia spectrum diagnosis [49,50]  Positive correlations have been found between self-disorders and positive symptoms, negative symptoms, formal thought disorders, and perceptual disturbances, respectively [43]  Correlations have been found between selfdisorders and social dysfunction [51] and suicidality [52,53], respectively  No correlations have been found between selfdisorders and IQ or neurocognitive measures [43,54,55], except for impaired verbal memory [54]  Self-disorders have been found to be temporarily stable over a 5-year period [56] …”
Section: Summary Of Empirical Resultsmentioning
confidence: 97%